PENERAPANÃÂ PANELÃÂ PERAGAÃÂ MULTIÃÂ FUNGSIÃÂ SISTEMÃÂ KELISTRIKANÃÂ BODIÃÂ UNTUKÃÂ MENINGKATKANÃÂ KOMPETENSIÃÂ MAHASISWAÃÂ BIDANGÃÂ KELISTRIKANÃÂ BODIÃÂ - Widjanarko, DwiÃƒÂ‚Ã‚Â ; AbdurrahmanÃƒÂ‚Ã‚Â , -; WahyudiÃƒÂ‚Ã‚Â , - (Jurnal Pendidikan Teknik Mesin, 2010)
Tujuan penelitian ini untuk merancang dan membuat panel peraga sistem kelistrikan bodi multi ÃÂ fungsiÃÂ dan ÃÂ meneliti ÃÂ peningkatan ÃÂ kompetensi ÃÂ sistem ÃÂ kelistrikan ÃÂ bodi ÃÂ mahasiswa ÃÂ setelah ÃÂ menggunakan ÃÂ panel ÃÂ peraga.ÃÂ Metode ÃÂ yang ÃÂ digunakan ÃÂ dalam ÃÂ penelitian ÃÂ ini ÃÂ adalah metode ÃÂ pengembangan ÃÂ yang ÃÂ dilakukan ÃÂ dengan merancang,ÃÂ membuat ÃÂ dan menguji ÃÂ panel ÃÂ peraga ÃÂ sistem ÃÂ kelistrikan ÃÂ bodi multi ÃÂ fungsi, menerapkan ÃÂ panel ÃÂ peraga, melakukanÃÂ penelitian dengan metode quasiÃÂexperiment model oneÃÂgroup time series design. Pembelajaran dilaksanakan dalamÃÂ dua tahap, pertama pembelajaran tanpa menggunakan panel dan kedua dilakukan dengan dilengkapi panel peragaÃÂ multi fungsi. Hasil penelitian menunjukkan bahwa kompetensi mahasiswa setelah menggunakan panel peraga lebihÃÂ tinggi dibanding sebelum menggunakan panel peraga. Ini menunjukkan bahwa alat peraga sistem kelistrikan bodiÃÂ multi ÃÂ fungsi dapat membantu mahasiswa dalam meningkatkan ÃÂ kompetensi ÃÂ sistem ÃÂ kelistrikan bodi. PeningkatanÃÂ kompetensi setelah penggunaan alat tersebut sekitar 31,87%.Kata kunci: peraga multi fungsi, sistem kelistrikan bodiÃÂ The objectives of this research are to design and to make multifunctional ÃÂ body ÃÂ of ÃÂ electrical ÃÂ systemÃÂ teaching ÃÂ aids ÃÂ and ÃÂ to ÃÂ research ÃÂ the ÃÂ improvement of ÃÂ studentsÃ¢â¬â¢ ÃÂ competence on ÃÂ student body ÃÂ electrical ÃÂ system ÃÂ afterÃÂ using ÃÂ the ÃÂ teaching aids. The method used ÃÂ in ÃÂ this research ÃÂ is developing research done by designing, making, andÃÂ testing ÃÂ the ÃÂ teaching ÃÂ aids ÃÂ of multifunctional ÃÂ body ÃÂ electrical ÃÂ system, ÃÂ applying ÃÂ the ÃÂ teaching ÃÂ aids ÃÂ in ÃÂ teaching ÃÂ andÃÂ learning ÃÂ process, ÃÂ carrying ÃÂ out ÃÂ the ÃÂ research ÃÂ using ÃÂ quasy ÃÂ experimentwith ÃÂ model ÃÂ one ÃÂ group ÃÂ time ÃÂ series ÃÂ design.ÃÂ Teaching and learning process are held in two stages, first is ordinary ÃÂ teaching and ÃÂ learning process without ÃÂ theÃÂ teaching aids and the second is teaching and learning process with the teaching aids. The result indicates that theÃÂ studentsÃ¢â¬â¢ competence after using the teaching aids in the teaching and learning process gets higher than before theÃÂ application of teaching aids. This shows that the teaching aids could help students in improving their competenceÃÂ in body electrical system. The improvement is about 31,8%.Keywords: multifunctional teaching aid, body electrical system